The lost self (Al _shanfara as a Model) (Journal of the College of Basic Education, 2026)
Shanfara held a high position in his tribe.He was its voice and the defender of its existence towards other tribes.Hence ,his existence was linked to his tribe as part of its social structure ,which bore the responsibility of elevating the status of that tribe before others and defending it , in the face of him ,if something happened to it .of the is one shanfara hard to (vagrant)poets who strove break out of the prevailing social system that was unjust to them ,as they believed,and to search for their existence , especially in his (Lamiyyah) ,which is a model that can be relied upon.